Farmers, Markets and Contracts: Chain Integration of Smallholder Producers in Costa Rica - Ruben, Ruerd; Sáenz-Segura, Fernando (European Review of Latin American and Caribbean Studies, 2008)
Contract farming is frequently considered as an appropriate mechanism for integrating smallholders into dynamic markets. We discuss the rationale for the variety in contractual arrangements between small-scale producers and agro-processing firms in the Northern and Central region of Costa Rica. Different market configurations give rise to delivery conditions, ranging from spot market negotiations to verbal or written contracts. We analyse which types of farmers are typically engaged in each of these contractual arrangements, and what are the implications for their production and investment decisions. Main attention is given to the effects of institutional organization for equity, efficiency and sustainability. The analysis is based on detailed case studies for two non-traditional commodities (pepper and chayote). Results suggest that contracts provide an important insurance device for farmers meeting investment and information constraints, and offer incentive for more intensive input use. This suggests that contract farming may be a critical requirement enabling smallholders to enter into specialized markets.Resumen: Campesinos, mercados y contratos: La integración al mercado de los pequeños productores de Costa RicaFrecuentemente se considera a la agricultura de contrato como un mecanismo apropiado para fomentar la integración campesina en mercados dinámicos. Discutimos los fundamentos que explican la gran variedad en arreglos contractuales entre pequeños productores y empresas agroindustriales en la zona Norte y Central de Costa Rica. Diferentes configuraciones mercantiles inducen condiciones de suministro que varían entre negociaciones en el mercado mismo hasta contratos verbales y escritos. Aquí analizamos qué tipo de productores se relacionan normalmente en cada uno de estos arreglos contractuales, y cuáles son las implicaciones para sus decisiones de producción e inversión. Prestamos especial atención a los efectos de la organización institucional para la equidad, la eficiencia y la sostenibilidad. El análisis está basado en estudios de caso de dos rubros no-tradicionales (pimienta y chayote). Los resultados indican que los contractos ofrecen una importante opción de seguro para productores con limitaciones de inversión e información, y generan incentivos para intensificar el uso de insumos. Eso implica que la agricultura de contrato puede ser un requerimiento vital para facilitar la integración campesina en mercados especializados.